La presse et la jeunesse en Syrie : la sortie du silence…mais pas encore le droit à la parole - Rama Najmeh (Revue des Mondes Musulmans et de la Méditerranée)
In a country where more than half the population is less than 30, the press should play a major role as a forum for debates, as a place for the emergence of new projects and personalities, and as a link between young people and politics. But if the Syrian press was actually born at the beginning of the 20th century thanks to the initiative of a group of young modernist intellectuals, in the political context of post independance years it soon became ideological and ossified, and a mere expression of the ba’thist regime, an organ for propaganda, submitted to severe procedures of censorship and self-censorship. But these ossified slogans did not succeed in mobilising the public and the youth did not recognize itself in such a press. On the contrary, young people refrained from any public activity, feeling strongly defiant towards politics. Nevertheless, the new permission to publish private newspapers in 2001, the emergence of a new generation of journalists and the development of internet news sites have started to offer them new opportunities.